PENGARUH STORE ATMOSFER DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA LADYFAME SHOP BANDAR LAMPUNG - Anindia, Zakia Nada; Siltra, Didi; Palupi, Alifah Lesi; Sanjaya, Vicky F (Faculty of economcs Universitas Singaperbangsa Karawang, 2023)
Problems faced by the ladyfame shop, namely related to the atmosphere of the shop, such as the shop being not big and spacious enough, so that the space for consumers to move is limited, especially at times when there are lots of visitors, such as before holidays: a narrow space will certainly limit the space for visitors to move. This certainly disrupts visitor comfort because visitors cannot freely choose the clothes they want. This phenomenon can also be seen, based on research results which state that the indoor air temperature at Ladyfame makes consumers uncomfortable, and this can influence consumer purchasing decisions. Apart from store atmosphere, location can also be a factor that can influence consumer purchasing decisions. In the process of determining where a Buyer will see that location factors will be determining. Buyers tend to choose to shop at stores that have strategic locations. The population in this study were consumers who had shopped at the Ladyfame Shop. The sample for this research consisted of 90 respondents. The approach used in this research is a quantitative approach. Quantitative data is data in the form of a questionnaire and then the data is processed using smartpls 4. The results of this research show that the store atmosphere has a positive and significant influence. Based on the data testing that has been carried out, the results show that the store atmosphere has a positive and significant influence, while the location has a negative and no influence Significant.